Thinking About the Future: A Review of Prognostic Scales Used in Acute Stroke - Drozdowska, Bogna A.; Singh, Sarjit; Quinn, Terence J. (Frontiers in Neurology, 2019)
Background: Many prognostic scales aiming to predict functional outcome following acute stroke have been described. Despite considerable research interest, these scales have had limited impact in routine clinical practice. This may be due to perceived problems with internal validity (quality of research), as well as external validity (generalizability of results). We set out to collate information on high profile stroke prognosis scales giving particular attention to their derivation, content and validation. Methods: We performed a focused literature search to find high profile scales that use baseline clinical data to predict mortality or disability. We described prognostic utility and collated information on the development, validation and content of the tools. We critically appraise chosen scales based on recommendations from the CHecklist for critical Appraisal and data extraction for systematic Reviews of prediction Modelling Studies (CHARMS). Results: We chose ten primary scales that met our inclusion criteria, six of which had revised versions. Most primary scales used 5 input variables (range: 4 – 13), with substantial overlap in the variables included. All scales included age, eight included a measure of stroke severity, while five scales incorporated pre-stroke level of function (often using modified Rankin Scale), comorbidities and classification of stroke type. Through our critical appraisal of included scales, we found that the most common issues increasing risk of bias related to excluding patients with missing data from derivation studies, and basing variable selection on significance of associations with the outcome in univariable analysis (in both cases noted for six studies). We identified separate external validation studies for all primary scales but one, with a total of 60 validation studies. Conclusions: A variety of prognostic scales exist for stroke. Most use similar variables to predict long-term outcomes and most have reasonable prognostic accuracy. While not all published scales followed best practice in development, most have been subsequently validated. Lack of clinical uptake may relate more to practical application of scales rather than validity. Impact studies are necessary to investigate clinical usefulness of existing scales.